SISTEM INFORMASI FASILITAS DI DKI JAKARTA BERBASIS ANDROID DENGAN ALGORITMA FLOYD WARSHALL - Rachman, Ali; Leidiyana, Henny (Universitas Muhammadiyah Magelang, 2020)
Mobile devices, especially the Android operating system, are very easy to use to provide information related to work or location precisely and accurately, especially searching for the location of facilities in DKI Jakarta, such as hospitals, fire stations, restaurants, hotels, and other places. But so far the problem is often encountered related to inaccurate information reports where reports take the form of images and text without a real location statement. For this reason, it is necessary to design a mobile application that can provide detailed information about the location of several public facilities in DKI Jakarta using the Software Development Life Cycle (SDLC) method. Applications that are made can provide information that has several features including image information, title, description, location, and weather.